KISAH ADAM DALAM AL-QUR’AN (KAJIAN SEMIOTIK) - Arif Budiono (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstract: This article aims to explain the story of Dam who is classified as Qaṣaṣ 'an al-Ghaybiyyah al-Mâdiyyah, namely a metaphysical story that occurred in the past. This story is a miniature picture of human life while living on earth. The story of Âdam can be classified as a group of mutashabihat verses, of eschatological value because no information is found from the al-Qur'an regarding the story of Dam's life after coming to earth, except for fragments of the story of two sons of Dam. The story of Âdam can be understood as a tamthîl (imaginary) story. That is, what is meant in the narrative description is not the story line textually, but what is wanted is what is symbolized by the text itself. Because the purpose of the story of the Qur'an is not the interest of the story itself in the framework of historical chronology, but the purpose of the story is to provide 'ibrah, advice and lessons for humans. This research is intended to find out how the structure of the Damn story in the Qur'an and the philosophical messages contained in it, as well as to what extent the contribution of semiotics as an approach to modern linguistic interpretation in providing new offers, in the form of interpretations that are different from existing interpretations.Keywords: Adam, Semiotic, Tafsir